The effect of understanding by design-based learning design with priority program in increasing endurance - Ilyas Khatib Firmansyah; Resty Gustiawaty; Suprananto Suprananto (Universitas Sriwijaya, 2025)
Research Problems: Cardiovascular endurance is needed when learning sports because when you have good cardiovascular endurance, you will not feel tired easily when learning in PE. In addition, good endurance is expected to improve the quality of learners with the advancement of scientific and technological fields. Research Objectives: This research seeks to assess the impact of Understanding By Design-based Learning Design with the Priority Program on Increasing Power in class VIII students at SMP Negeri 4 Klari. Methods: The approach taken in this study is a quasi-experimental design involving two groups with assessments before and after the intervention. A total sample of 72 was taken from each class of 36 students. Data collection for this study was conducted using a beep test adopted from the Indonesian Student Fitness Test (TKSI). After that, treatment was given for 6 meetings and a posttest using the beep test. Results: The findings indicated that there was a notable impact of Understanding By Design-based learning design with a priority program in increasing endurance In the class that was tested versus the class that was used for comparison, where in the tested class there was an increase in endurance of 26 students while in the experimental class only 7 students increased. Conclusion: Overall, the improvement experienced by the experimental class was uneven, so this needs to be considered in further research to take a more appropriate method so that the improvement experienced by students is maximised.